Searching for New Human Behavior Model in Explaining Energy Transition: Exploring the Impact of Value and Perception Factors on Inconsistency of Attitude toward Policy Support and Intention to Pay for Energy Transition - Oh, Yoonjung; Kim, Seoyong; Kim, Sohee (International Journal of Environmental Research and Public Health, 2022)
The purpose of this study is to compare and analyze the factors influencing the public’s attitude toward policy support and intention to pay for energy transition from nuclear to renewable energy. We focus on inconsistency issues between attitude and intention. To this end, we set the attitude toward policy support and behavioral intention to pay as dependent variables, and value factors (i.e., ideology, political support for the current Moon Jae-in government, environmentalism, and science-technology optimism) and perception factors (i.e., perceived risk, benefit, knowledge, and trust) as the independent variables. Based on a survey, the analysis showed that at the variable level, the perceived benefits and trust in renewable energy and perceived risks and benefits in nuclear energy influenced the attitude toward policy support and the intention to pay for energy transition. Second, when evaluating the explanatory power of independent variables, the attitude toward the energy transition was affected in the following order: (1) perceived benefit in nuclear power (β = 0.259) > (2) perceived benefit in renewable energy (β = −0.219) > (3) perceived risk in nuclear energy (β = 0.202) > (4) Moon Jae-in government support (β = 0.146). On the other hand, behavioral intention to pay for energy transition was influenced in the following order: (1) trust in renewable energy (β = 0.252) > (2) Moon Jae-in government support (β = 0.154) > (3) perceived risk in nuclear energy (β = 0.139) > (4) perceived benefit in renewable energy (β = 0.099). Third, variables such as environmentalism, perceived benefit/risk/trust in renewable energy, and perceived benefit/risk in nuclear energy affected inconsistency between attitude toward policy support and intention to pay for energy transition.
Keywords: Attitude; Humans; Intention; Perception; Policy; Surveys and Questionnaires; attitude toward policy support; attitude-intention consistency; energy transition; intention to pay; value